Strengthening anti-corruption efforts for the digital native generation based on the path analysis model - Djulya Eka Pusvita; Arini Asriyani; Surya Dharma; Didin Wahyudi (Komisi Pemberantasan Korupsi, 2025)
The results of observations on the digital native generation indicate a problem in which students generally have limited understanding of the impacts of corruption and tend to believe that corruption only occurs at the governmental level, having no direct relevance to their personal lives. Based on this issue, it is important to explore the factors that may influence anti-corruption behavior among digital natives, particularly because variables such as digital legal literacy, character education, and teacher performance have rarely been examined comprehensively in this context. Therefore, this study aims to investigate the crucial mediating role of digital legal literacy in the relationship between character education and teacher performance in shaping anti-corruption behavior among digital native students. This research employed a quantitative approach by developing a path analysis model. The population consisted of digital native students enrolled at the senior high school level in Gowa Regency. Data were collected using a Likert-scale questionnaire, and the data analysis technique used was path analysis. The findings reveal that digital legal literacy plays a significant mediating role in the influence of character education and teacher performance on shaping anti-corruption behavior among digital native students at the senior high school level.